PANCA SATYA OF HANUMAN CHARACTER IN THE RAMAYANA - Ni Ketut Riska Dewi Prawita; I Wayan Dikse Pancane; I Gede Suwantana; I Gede Wangga Putrayasa (UHN I Gusti Bagus Sugriwa Denpasar, 2024)
Various sources of yoga literature that are still relevant today are used by yoga practitioners and academics in developing this realm of logical and practical thinking, such as: Vedanta, Bhagavad Gita, Siva Samhita, Yoga Vasista, Goraksasatakam, Gheranda Samhita, Hatha Yoga Pradipika, Sutra Patanjali, Upanishads, Ramayana, Mahabrata and various Balinese local wisdom belonging to the Sivaistik lontars. These sources of yoga literature make yoga not only traceable through its practical aspects but also allow for a search of the philosophical aspects of yoga implied in these literary sources so that yoga academics and practitioners can increase their knowledge and understanding of the scope of yoga teachings. This study aims to analyze the depth of the philosophy and practice of yoga contained in the Siva Samhita. The theories used are the theory of philosophy and semiotic theory. This study uses the method of collecting documents and literature. The data analysis technique was carried out qualitatively by describing it descriptively. The results of this study indicate that: (1) the study of yoga metaphysics contained in the Siva Samhita script is a study of God, maya, the soul, the microcosm of the body, and the nature of karma; (2) the study of the epistemology of yoga in the Siva Samhita script covers the nature of knowledge, the importance of the role teacher and the nature of liberation.